Development of Android-Based Learning Media First-Aid Learning in Accidents for SMP Extracurriculars - Arif Al Anshari; Suparno Suparno (Postgraduate School, Universitas Negeri Padang, 2020)
The purpose of this research is to produce learning media based on android that is valid, practical, and effective. This type of research is development. The development model used is the 4-D model, consisting of four stages, namely define, design, develop, and disseminate. The research data were obtained from validity, practicality, and effectiveness tests. From the results of the media validity test, it shows that the category is very valid from 3 aspects, namely the material aspect of 97.89%, the media aspect of 81.82%, and the language aspect of 82.86%. Practicality data were obtained from the results of the questionnaire analysis of the responses of educators and students, while the practicality test results of Android-based learning media for first aid learning obtained an assessment of 93.40 for practicality assessment by students and 96.67 for practical assessment by educators with a very valid category. The results of the effectiveness test of student learning outcomes pretest results obtained an average of 62.25 and at the time of the posttest increased to 83.25 after using android-based learning media in the learning process of first aid in accidents, this shows that there is an increase in student learning outcomes after using based learning media. android learning first aid for junior high school extracurricular accidents.